2021
DOI: 10.1002/bse.2862
|View full text |Cite
|
Sign up to set email alerts
|

The effects of regional trade integration and renewable energy transition on environmental quality: Evidence from South Asian neighbors

Abstract: Improving environmental quality across South Asia has become one of the utmost important policy agendas of the concerned governments. The susceptibility of the majority of the South Asian countries to multifaceted climate change adversities has motivated the need to identify the factors that can function to ensure environmental sustainability across South Asia. Although several studies have highlighted the importance of globalization and cleaner energy use in tackling the environmental degradaton issues of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 93 publications
1
25
0
Order By: Relevance
“…For example, Wang ( 2012 ) has investigated the panel data of 98 countries around the world from 1971 to 2007 and found that under a slow economic growth system, economic growth has a negative impact on CO 2 emissions; under a modest economic growth system, economic growth has a positive impact on CO 2 emissions growth; and under a rapid economic growth, the impact on economic growth is minimal (Charfeddine and Kahia, 2019 ). This result is consistent with the study of Murshed et al ( 2021a ), who concluded that economic growth promotes increased carbon emissions in the long run, but trade between neighboring countries has a positive role in reducing carbon emissions. On this basis, Khan et al found that economic growth in RCEP countries has a dampening effect on CO 2 emissions and supports the environmental Kuznets curve (EKC) hypothesis by studying the role of export diversification and compound country risk in carbon emission reduction.…”
Section: Literature Reviewsupporting
confidence: 93%
“…For example, Wang ( 2012 ) has investigated the panel data of 98 countries around the world from 1971 to 2007 and found that under a slow economic growth system, economic growth has a negative impact on CO 2 emissions; under a modest economic growth system, economic growth has a positive impact on CO 2 emissions growth; and under a rapid economic growth, the impact on economic growth is minimal (Charfeddine and Kahia, 2019 ). This result is consistent with the study of Murshed et al ( 2021a ), who concluded that economic growth promotes increased carbon emissions in the long run, but trade between neighboring countries has a positive role in reducing carbon emissions. On this basis, Khan et al found that economic growth in RCEP countries has a dampening effect on CO 2 emissions and supports the environmental Kuznets curve (EKC) hypothesis by studying the role of export diversification and compound country risk in carbon emission reduction.…”
Section: Literature Reviewsupporting
confidence: 93%
“…Hence, initially, a small gain in the energy efficiency level, synonymous with technological development in the preliminary phases, may not be sufficient in enhancing access to modern cooking fuels such as LPG. For instance, the extraction of LPG from natural gas production or during oil refining requires the application of the latest technology [70,71]. In contrast, the use of conventional solid biomass and firewood for cooking purposes does not require technological progress to a large extent.…”
Section: Discussion On the Findingsmentioning
confidence: 99%
“…This is because the developing countries are predominantly fossil fuel-intensive whereby a lion's share of their respective electricity outputs from gas, coal, and furnace oils (Rehman et al 2019;Murshed and Tanha 2021;Murshed et al 2021a). Besides, it is believed that the developing countries, in quest of globalization, tend to prioritize attainment of economic growth at the cost of environmental degradation (Murshed 2020a, b;Murshed et al 2021bMurshed et al , 2021c. Hence, under such circumstances, the execution of the BRI can be hypothesized to cause environmental distress across the developing countries that are members of this initiative.…”
Section: Introductionmentioning
confidence: 99%